Noragami : Stray god, 14 - Adachi, Toka (Kodansha Comics, 2016)
"Hiyori and her family are still dealing with the repercussions of the hospital disaster, and Yato is convinced Hiyoris troubles are all his fault. He runs away, vowing never to see her again until he is a genuine god of happiness. Meanwhile, Bishamon is having fallout problems of her own&"--Pg. 4 of cover.